Se nourrir à Hanoi : les recompositions du système alimentaire d’une ville émergente - Gwenn Pulliat (EchoGéo)
If the Vietnamese capitale city primiraly benefits from the shifts in which the economic takeoff of Vietnam has resulted since early 1990, analyzing the food system sheds light on the way that mutations of this emerging city impact people’s food practices. It reveals a two-tiered city: Hanoi is more and more engaged into international markets but familial farming is persistent; markets are involved in a modernizing process but street vending is still important; food transition has begun but food insecurity remains. The example of food shows how mutations of Hanoi deepen social inequalities.